History of the Decline and Fall of the Roman Empire $1 (BVolume 3s - Gibbon, Edward, 1737-1794; Milman, Henry Hart, 1791-1868 (Salt Lake City, UT : Project Gutenberg, 2008)
"History of the Decline and Fall of the Roman Empire $1 (BVolume 3" by Edward Gibbon is a historical work published in 1781. This volume continues Gibbon's monumental examination of Rome's collapse, tracing the empire from its zenith through early Christianity's rise, the Western Empire's fall, and beyond. Written with detached yet critical prose, Gibbon explores how civic virtue eroded and barbarian invasions succeeded. His controversial thesis about Christianity's role sparked immediate debate, while his Enlightenment perspective dismissed the Middle Ages as a superstitious Dark Age awaiting reason's return. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_History_of_the_Decline_and_Fall_of_the_Roman_Empire
Release date is 2008-06-07
David Reed and David Widger
Keywords: Rome -- History -- Empire, 30 B.C.-476 A.D.; Byzantine Empire -- History -- To 527